Pneumococcal association to platelets is mediated by soluble fibrin and supported by thrombospondin-1 - Niemann, Silke; Kehrel, Beate E.; Heilmann, Christine; Rennemeier, Claudia; Peters, Georg; Hammerschmidt, Sven (Thrombosis and Haemostasis, 2009)
Platelets and coagulation are involved in bacterial colonisation of the host. Streptocococcus pneumoniae (pneumococcus) are important etiologic agents of respiratory tract infections in humans. The formation of pneumococci-platelet associations may facilitate haematogenous dissemination of pneumococci by providing an adhesive surface on damaged endothelium. However, the formation of platelet-pneumococci associations and the factors involved in this process have not been described so far. The formation of platelet-pneumococci associates was analysed and quantified using flow cytometry. Binding of pneumococci to platelets was significantly increased after activation of platelets with thrombin, while platelet activation by ADP or collagen did not promote formation of platelet-pneumococci associates. In addition to be a platelet agonist, thrombin cleaves fibrinogen, which results in the generation of fibrin. The simultaneous formation of fibrin and activation of platelets was shown to be a prerequisite for a high number of platelet-pneumococci associates. Moreover, exogenously added human thrombospondin-1 (TSP-1) significantly enhanced the association of pneumococci with activated platelets. Soluble fibrin and TSP-1 are key co-factors of platelet-pneumococci-association. Similar results were recently demonstrated for S. aureus-platelet adhesion. Consequently, we hypothesise that the described mechanism of platelet-bacteriaassociation might represent a general and important strategy of Gram-positive bacteria during development of invasive diseases.
Keywords: Platelets; Streptococcus pneumoniae; Gram-positive bacteria; fibrin; thrombospondin-1